2008
DOI: 10.1007/s11814-008-0091-5
|View full text |Cite
|
Sign up to set email alerts
|

Application of spent sulfidic caustics for autotrophic denitrification in a MLE process and their microbial characteristics by fluorescence in situ hybridization

Abstract: Spent sulfidic caustics (SSCs) produced from petrochemical plants contain a high concentration of hydrogen sulfide and alkalinity, and some organic matter. Most of the SSCs are incinerated with the auxiliary fuel causing secondary pollution problems. The reuse of this waste is becoming increasingly important in terms of economical and environmental viewpoints. To denitrify wastewater with a low COD/N ratio, additional carbon sources are required. Therefore, autotrophic denitrification has received increasing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Park et al [29] reported that the optimum dosage of SSC was below an S/N ratio of 2.5 and excess SSC injection induced nitrification failure because the caustic content is higher than required. Based on these results, the pH of SSC was neutralized from approximately 13.3 to 12.0 with the addition of sulphuric acid (H 2 SO 4 ), after which the neutralized SSC was injected into the anoxic tank.…”
Section: Toxicity Experimentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Park et al [29] reported that the optimum dosage of SSC was below an S/N ratio of 2.5 and excess SSC injection induced nitrification failure because the caustic content is higher than required. Based on these results, the pH of SSC was neutralized from approximately 13.3 to 12.0 with the addition of sulphuric acid (H 2 SO 4 ), after which the neutralized SSC was injected into the anoxic tank.…”
Section: Toxicity Experimentsmentioning
confidence: 99%
“…As the SSC dosage increased, SOUR decreased. Park et al [29] reported that 4 mL/L of SSC dosage was the optimum dosage for autotrophic denitrification. The slight reduction in SOUR was observed until the injection of 4 mL/L of SSC.…”
Section: Inhibition Of Ssc To Microorganism Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays physicochemical methods such as wet air oxidation (WAO), advanced oxidation and the MEROX process, as well as biological methods are proposed for the treatment of sulfidic spent caustic [17][18][19][20]. among which biological systems could be advantageous due to lower cost and higher safety [21].The limited number of researches conducted on the biotreatment of sulfidic spent caustic mostly focused on the application of neutrophilic sulfur bacteria belonging to the genus Thiobacillus, where the stream needs to be diluted in order to decrease the pH and salinity levels [16,[22][23][24]. On the other hand, at pH levels below 9, most of the dissolved sulfide would be released as toxic hydrogen sulfide into the atmosphere [25,26].…”
Section: Introductionmentioning
confidence: 99%